Ответ:
не знаю, нужно ли расписывать 49 и 50, но сделал на всякий случай, а там смотри сам.
Объяснение:
42. (4x-1)(4x+1)
43. (t-p)(t+p)
44. (a-5b)(a+5b)
45. (7z-11t)(7z+11t)
46. (12y-9)(12y+9)
47. (a[tex]d^{3}[/tex]-3)(a[tex]d^{3}[/tex]+3)
48 ([tex]x^{2}[/tex][tex]y^{2}[/tex]-1)([tex]x^{2}[/tex][tex]y^{2}[/tex]+1)
49. ((a+k)-(a-k))((a+k)+(a-k))=(a+k-a+k)(a+k+a-k)=2k*2a=4ak
50. (5t-(2z+3t))(5t+(2z+3t))=(5t-2z-3t)(5t+2z+3t)=(2t-2z)(8t+2z)=2(t-z)2(4t+z)=4(t-z)(4t+z)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
не знаю, нужно ли расписывать 49 и 50, но сделал на всякий случай, а там смотри сам.
Объяснение:
42. (4x-1)(4x+1)
43. (t-p)(t+p)
44. (a-5b)(a+5b)
45. (7z-11t)(7z+11t)
46. (12y-9)(12y+9)
47. (a[tex]d^{3}[/tex]-3)(a[tex]d^{3}[/tex]+3)
48 ([tex]x^{2}[/tex][tex]y^{2}[/tex]-1)([tex]x^{2}[/tex][tex]y^{2}[/tex]+1)
49. ((a+k)-(a-k))((a+k)+(a-k))=(a+k-a+k)(a+k+a-k)=2k*2a=4ak
50. (5t-(2z+3t))(5t+(2z+3t))=(5t-2z-3t)(5t+2z+3t)=(2t-2z)(8t+2z)=2(t-z)2(4t+z)=4(t-z)(4t+z)